ABOUT CARDIOLOGY AND LIFE: INTERVIEW WITH AN INTERESTING CHARACTER MEDICATION SHOULD BE A PART OF THE HUMAN ORGANISM (INTERVIEW WITH E.I. CHAZOV) - N. V. Dolgushina (Столичная издательская компания, 2015)
.